The Effect of Capital Structure, Firm Age, Firm Size, Asset Structure, Liquidity, Financial Slack, Asset Productivity, and Operating Profit Margin on Profitability - WELLY, Welly; HERMANTO, Hermanto (PT Keberlanjutan Strategis Indonesia, 2025)
This research aims to analyze the effect of capital structure (SM), company age (AGE), company size (SIZE), asset structure (TANG), liquidity (CR), financial slack (SLACK), asset productivity (PA), operating profit margin (OPM) on profitability in energy sub-sector companies listed on the Indonesia Stock Exchange (IDX) in 2020-2024. Data were obtained from financial reports published by the company, with a total of 105 data from 21 companies selected as samples using purposive sampling techniques. Data analysis through multiple linear regression using the Eviews12 statistical data processing application. The results of the study suggest that capital structure, asset structure, liquidity, financial slack have no effect on profitability. While company age and company size have a negative impact on profitability while asset productivity and operating profit margin have a positive and significant impact on profitability.